Directors’ duties to creditors - Lombard, Sulette (University of Pretoria, 2007)
Creditors of the corporate business form are in a vulnerable position. Recognition of the plight of corporate creditors led to the implementation of various legal measures aimed at protecting their financial interest in the company. These measures proved disappointingly inadequate in many instances. As a result the judiciary in some jurisdictions felt compelled to develop existing legal principles pertaining to directors’ duties in such a way that they could be used to facilitate protection of corporate creditors’ interests. This development did not meet with universal approval. Those opposed to the extension of directors’ duties to protect creditors’ interests have three main arguments against it. The first is related to conceptual issues and policy concerns. The second argument is that existing remedies are more than adequate to protect creditors’ interests. A last argument against a directorial duty to creditors pertains to the practical implementation of this extended duty. It is argued that the existing legal framework with regard to directors’ duties is not suitable to provide protection for creditors’ interests. However, it was shown in this study that the extension of directors’ duties to protect creditors’ interests is indeed justifiable on a sound conceptual basis and that policy concerns regarding such an extension are either unfounded, or should be addressed in some other way. An analysis of existing protective measures and remedies often referred to by opponents of an extension of directors’ duties, namely statutory personal liability of directors, traditional insolvency remedies, and the piercing of the veil doctrine furthermore showed that these measures are inadequate. This leads to the conclusion that there is a definite need for an alternative remedy, such as the extension of directors’ duties to include creditors’ interests. The existing legal framework in respect of directors’ duties furthermore proved to be capable of being successfully adapted to include creditors’ interests. Central issues in this respect, as was indicated by an analysis of case law, are the point in time when the duty to creditors is triggered, the beneficiary of the duty, in other words who would have locus standi in case of a breach of the duty, and the type of protection afforded to creditors’ interests by way of fiduciary duties and the duty of care and skill. The existing legal framework also provides measures in terms of which honest and diligent directors may be relieved from liability, such as indemnification, relief granted by the courts and director liability insurance. These measures, if formulated correctly, may achieve and maintain the essential balance between accountability and entrepreneurial freedom. The legislature appears to have adopted a cautious approach to the issue of directors’ duties to creditors. It thus seems to be up to the judiciary to develop directors’ duties to creditors in a meaningful way. Pioneering in this respect has already been done in Australia, New Zealand, England, Canada and the United States of America. It is to be hoped that the South African judiciary will follow suit when the opportunity to do so arises.
Keywords: Beneficiary of directors’ duties; Company law; Company’s interests; Corporate law

The Harmonization of Business Law in Africa: Is Article 42 of the OHADA Treaty a Problem? - Enonchong, Nelson (Journal of African Law, 2007)
OpenAlex: https://openalex.org/W2023472476
Keywords: Harmonization; Investment; Member state

Legal aspects of corporate governance in the republic of South Africa: towards a possible model for improved stakeholder relations within the corporation - Spisto, Michael Paolo (University of the Witwatersrand, 2007)
Traditionally, company law assumes that the directors’ role is to run the company for the benefit of its shareholders alone and to maximise profits for them. It can be argued, however, that this view is too narrow and outdated; that is, company directors should have regard to the rights and interests of a broader range of corporate stakeholders. Hence, the question is whether we should change our perception of the company or corporation from one run by directors dedicated exclusively to serving the interests of shareholders to that of a corporation whose main purpose is to bring benefit not only to its owners and creditors, but also to its employees, the community and the environment. Given that reforms of directors’ duties in light of the above considerations have found their way into legislation across the globe, this thesis examines how and to what extent legal rules and policies should develop in South Africa to place directors under a positive duty to take account of the interests of bodies other than shareholders. Current South African company law does not contain clear rules regarding corporate governance issues and the duties and liabilities of directors. These matters have been left to the common law and Codes of Corporate Practice. Thus, there is no extensive statutory scheme in South Africa, which covers the duties, obligations and accountability of directors. The focus in this thesis is on the rights and interests of employees and the premise that is defended is that it is valuable to corporations to provide employees with an institutionalised voice at board level. It is argued that there is global evidence that where employees participate in the decision-making processes of the company, performance is generally enhanced. This, in turn, directly impacts upon and improves economic productivity, generating a ‘win-win’ situation. The question of the duties of company directors and managers is attracting much attention in South Africa. With rapidly developing and changing labour legislation in South Africa, it is essential to consider the extent to which the country should reassess its traditional principles of company law and corporate governance policies in order to encourage participatory roles for employees in the workplace. It is argued that if South Africa is to improve corporate productivity levels with its re-entry into international markets, management and labour must find improved ways of dealing with one another. The main purpose of this thesis, therefore, is to propose and formulate a workable corporate governance model for South Africa – one that would be advantageous to all stakeholders, especially the employees. This is achieved by comparing and contrasting international models of corporate governance and by applying the best features of each to the unique South African corporate system of values, structures and traditions. It is suggested that the current unitary board structure operating in South Africa has become outdated and does not provide employees with rights enabling them to engage in the decision-making processes of the corporation with their employees at an adequate level. In its place, a two-tier board system of corporate governance is proposed. The economic success of a company will bring about social benefits to many stakeholder constituencies. This will not happen if the company is a financial failure. The issue of obliging directors to act primarily for the benefit of shareholders alone is questioned. Corporate governance reforms were undertaken in many parts of the world in the late 1980’s and early 1990’s. This reform process questioned whether the interests of the company should be managed for the shareholders alone or for the other corporate stakeholders as well. There are many views that strongly support the idea that corporate governance should be seen as a system by which corporations are to be governed for the benefits of all stakeholders, including shareholders, employees, creditors, suppliers and the community. In this way, companies should be run as communities in partnerships with all their stakeholders. Thus, this thesis proposes that the success of a company is inextricably intertwined with a consideration of the rights and interests of its employees and other stakeholders.
URI: http://hdl.handle.net/10539/1969
Keywords: Bond/Debenture Holders; Community; Companies; Corporate governance; Corporations; Creditors; Employees; Environment; Interests; Models; Rights; Shareholders; South Africa; Stakeholder Relations

Waiver of a Right to Arbitrate by Resort to Litigation, in the Context of International Commercial Arbitration - Gillies, Peter; Dahdal, Andrew (Journal of International Commercial Law and Technology, 2007)
This paper examines the circumstances in which a party to an arbitration agreement may be deemed tohave waived its right to arbitrate a dispute comprehended by the agreement, by involvement in litigation concerning this dispute. The focus is on the law in common law jurisdictions, particularly Australia and theUnited States of America. United Kingdom law will also be briefly surveyed. The paper focuses on the 2006 decision of the Australian Federal Court in Comandate Marine Corp v Pan Australia Shipping Pty Ltd, whichafforded the topic significant treatment. The theoretical bases for sustaining waiver claims are analysed, includingwaiver as a discrete doctrine, abandonment, estoppel, election, repudiation of contract and variation of contract.The policies that underlie and inform the development of principles for testing waiver submissions are noted.
https://www.neliti.com/publications/28634/

Accounting for financial instruments: An analysis of the determinants of disclosure in the Portuguese stock exchange - Lopes, Patrícia Teixeira; Rodrigues, Lúcia Lima (The International Journal of Accounting, 2007)
In this paper we analyse the determinants of disclosure level in the accounting for financial instruments of Portuguese listed companies. Considering the mandatory adoption of International Accounting Standards after 2005, our ultimate objective is to analyse the characteristics of companies that are closest to the disclosure requirements of IAS 32 and IAS 39. We have constructed an index of disclosure comprising 54 items based on IAS 32 and 39 disclosure requirements and computed the index score for each Portuguese listed company based on the analysis of the companies’ annual reports. We tested the relation between the index score and several firm-specific characteristics: size, industry, auditor type, listing status, multinationality degree, relationship shareholders/creditors and importance of shareholders. We conclude that larger companies and companies listed in more than one exchange market show higher levels of disclosure, meaning that they are closer to IAS 32 and 39 requirements. We argue that the agency theory, the signalling theory and the political costs theory do not fully explain Portuguese reality, where there is a large degree of family ownership and bank-oriented financing policies. We therefore advocate that the introducing variables related to specific characteristics of Portuguese companies and managers, in the context of other theoretical frameworks, notably the contingency theory, brings important insights to this type of analysis.

Small economies and their development in the Multilateral Trade System: correlation between economic and political environment and trade performance of small economies - Tiemeni, Thierry Galani (University of the Western Cape, 2007)
At the heart of this study is the topic of small economies in the Multilateral Trade System (MTS). The study examines the World Trade Organisation’s (WTO) legal framework and policy objectives in order to develop a comprehensive definition of small economies as a group of WTO members with specific needs. Particular attention is given to the determination of the specific characteristics of small economies, as well as the issues and constraints they are facing in the MTS. The study explores solutions proposed in order to tackle the constraints to the effective integration of small economies in the MTS, with specific reference to the policy reasoning of small economies. More importantly, the study explores the impact of the size factor, which is certainly not only a burden on the growth and development perspectives of the considered entity, but which may also become an advantage and promotes the trade performance of a small economy. Hypotheses are then made relating to the relevance of the economic and political environments in the determination of a successful (or not) integration, and participation, of a small economy in the MTS. A crucial argument developed is that the differences observed between countries sharing similar characteristics of smallness, vulnerability and remoteness/landlockedness, illustrates the fact that what ultimately matters is the interplay of factors related to the economic and political environments, the effect of which is to promote or constrain (depending on the case) successful integration of the small economy in the MTS.
https://hdl.handle.net/10566/18256
Keywords: Committee on trade and development; Developed countries; Economic environment; Multilateral trade system; Political environment; Small and vulnerable economy; Small economies; Trade performance; WTO; World Trade Organization

'Legal Traditions' and International Commercial Arbitration - Trakman, Leon (University of New South Wales, 2007)
Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration, the International Bar Association and the International Chamber of Commerce have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. More recent concerns have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it. Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration (ICA), the International Bar Association (IBA) and the International Chamber of Commerce (ICC) have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. From the doctrine of freedom of contract to specific rules of evidence and procedures that govern arbitral hearings, the international arbitration community has sought to maintain the respected legal traditions that lawyer-arbitrators and counsel find familiar and comfortable. More recent concerns, partly expressed by William K. Slate II, President of the American Arbitration Association, have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Are they sufficiently uniform in nature and operation to justify their dominant status in formulating codes, laws and rules governing international commercial arbitration? And has international commercial arbitration become unduly reliant upon both the Common and Civil Law traditions at the expense of other legal traditions that operate against the background of different and changing legal cultures? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it.
Télécharger l'article: https://www.austlii.edu.au/au/journals/UNSWLRS/2007/29.rtf